2022
DOI: 10.3390/ph15040428
|View full text |Cite
|
Sign up to set email alerts
|

Dual PI3K/Akt Inhibitors Bearing Coumarin-Thiazolidine Pharmacophores as Potential Apoptosis Inducers in MCF-7 Cells

Abstract: Breast cancer is the most common malignancy worldwide; therefore, the development of new anticancer agents is essential for improved tumor control. By adopting the pharmacophore hybridization approach, two series of 7-hydroxyl-4-methylcoumarin hybridized with thiosemicarbazone (V–VI) and thiazolidin-4-one moieties (VII–VIII) were prepared. The in vitro anticancer activity was assessed against MCF-7 cells adopting the MTT assay. Nine compounds showed significant cytotoxicity. The most promising compound, VIIb, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…In the present study, it was observed that coumarin 2k determined cell arrest of TPC-1 cells in the G2/M phase, indicating the apoptotic mode of cell death and inhibition of DNA synthesis (S phase reduction). This finding is consistent with previous investigations reporting that coumarins able to induce cytotoxicity by inducing G2/M and S phases arrest in different cancer cell lines [46,47].…”
Section: Effect Of Coumarins 2k and 2h On The Different Phases Of The...supporting
confidence: 94%
“…In the present study, it was observed that coumarin 2k determined cell arrest of TPC-1 cells in the G2/M phase, indicating the apoptotic mode of cell death and inhibition of DNA synthesis (S phase reduction). This finding is consistent with previous investigations reporting that coumarins able to induce cytotoxicity by inducing G2/M and S phases arrest in different cancer cell lines [46,47].…”
Section: Effect Of Coumarins 2k and 2h On The Different Phases Of The...supporting
confidence: 94%
“…Mechanistic studies based upon enzyme inhibition revealed the PI3K-α/Akt-1 axis as the target of the tested compounds, further confirmed by Western blot which evident the repressing levels of p-PI3K, Cyclin D1, and p-Akt computational studies illustrated the high binding affinity of compound 17a with PI3K binding site even superior to reference ligands X6K. The overall study proposed compound 17a as a potential anti-cancer against breast cancer by targeting PI3K/Akt axis, which can be further investigated [68].…”
Section: Anti-cancer Potential Of Di-substituted Thiazolidine-4-ones ...mentioning
confidence: 52%
“…Targeting this pathway for novel anti-cancer drug discovery has been a good rational and well-established approach [66,67]. Targeting the PI3K-Akt pathway, Abdelnaby et al [68] synthesized two series of compounds by molecular hybridization of coumarin with thiosemicarbazone and thiazolidine-4-one moieties (Figure 6). In the in-vitro anticancer screening against MCF-7 cells lines (via MTT assay), nine compounds displayed encouraging cytotoxicity, especially, compound 17a displayed promising cytotoxicity with IC50: 1.03 + 0.05 µM.…”
Section: Anti-cancer Potential Of Di-substituted Thiazolidine-4-ones ...mentioning
confidence: 99%
“…From the literature survey, both coumarin and cinnamic acid scaffolds have potential PI3K/AKT1 signaling pathway inhibitory action [ 64 , 65 , 66 , 67 ], and either coumarin derivatization or combination with cinnamic acid proposed the final compounds that possess the main pharmacophoric features as the bound ligands in the active site of both PI3K and AKT1. Generally, PI3K and AKT1 inhibitors have a common “hydrophobic-aromatic ring-hydrophobic-HB_A” feature as previously reported [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate secondary antibodies were incubated for 2 hr at room temperature. After being washed twice n 1× TBS-T, densitometric analysis of the immunoblots was performed to quantify the amounts of p-PI3K and p-AKT against the control sample by total protein normalization using Image analysis software on the ChemiDoc MP imaging system (version 3) produced by Bio-Rad (Hercules, CA, USA) [ 64 ].…”
Section: Methodsmentioning
confidence: 99%